ANALISIS PENDAPATAN USAHA BETERNAK AYAM RAS PEDAGING (BROILER) DI KABUPATEN KUBU RAYA, KALIMANTAN BARAT - B01107074, Firmansyah (Jurnal Pembangunan dan Pemerataan, 2014)
This research gets title â€œ Analys Chicken Continent Operating Revenues type(Broiler)Â  At Kubu Rayaâ€™s Fortification Regency â€. To the effect research is subject to be know and analyze is factor that regard Chicken continent effort production Pedaging's Race Broiler At Kubu Raya Fortification Regency, to know and analyze is production cost, analyze is cattleman income cost, analyze is influence total production cost to cattleman gain and analyze is Revenue BEP Break Even Point Chicken continent effort Close-fitting Broiler atÂ  Kubu Raya's Fortification Regency. In this study using descriptive methods, namely by describing the existing problems in the field and then analyzed the data and facts in the study. The technique of collecting data through observation processed and tabulated in the table. The analysis used in this study uses qualitative and quantitative analyze of respondents who took as many as 30 people broiler breeders Broiler. Of this research result, therefore gets to be concluded that capital and far ranging positive ascendant den to cattleman income.Â  Averagely production cost for each den extent Meter as big as Rp.101.088,- price sells broiler's chicken Kilogram is as big as Rp.19.000,- productions cost totaled influence to cattleman net earning at Regency Fortification Raya is positive so total production cost increase to be caused cattleman increases production amount foot up production therefore totaled revenue (TR) can at keeps on despite superordinate point total production cost increases, averagely BEP in Rupiahâ€™s as big as Rp. 1.129.32,-Â  and average BEP unit (Q ) as big as 59 Kilogram correspond tofoot up cost and acceptance amount every respondent. Key word: Spacious cage, Capital, Production cost, Revenue BEP